2020
DOI: 10.1101/2020.07.28.225912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infection of human lymphomononuclear cells by SARS-CoV-2

Abstract: Although SARS-CoV-2 severe infection is associated with a hyperinflammatory state, lymphopenia is an immunological hallmark, and correlates with poor prognosis in COVID-19. However, it remains unknown if circulating human lymphocytes and monocytes are susceptible to SARS-CoV-2 infection. In this study, SARS-CoV-2 infection of human peripheral blood mononuclear cells (PBMCs) was investigated both in vitro and in vivo. We found that in vitro infection of whole PBMCs from healthy donors was productive of virus pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 38 publications
5
75
1
2
Order By: Relevance
“…ACO1 was over-expressed in COVID-19 versus HC and under-expressed in non-COVID-19 viral infections versus HC, whereas ATL3 entirely oppositely regulated ( Figure 4 ). Viral replication can occur in infected cells due to a hinderance of the function of the immune cells drawn in to kill infected cells; as well, there are reports of SARS-CoV-1 and SARS-CoV-2 directly infecting immune cells themselves ( Gu et al., 2005 ; Hu et al., 2012 ; Pontelli et al., 2020 ). As our data are from whole blood RNA, we cannot conclude precisely which of these mechanisms are responsible for the shifts in these genes' expression; however, prior reports suggest that both genes may be involved in viral replication and immune evasion.…”
Section: Discussionmentioning
confidence: 99%
“…ACO1 was over-expressed in COVID-19 versus HC and under-expressed in non-COVID-19 viral infections versus HC, whereas ATL3 entirely oppositely regulated ( Figure 4 ). Viral replication can occur in infected cells due to a hinderance of the function of the immune cells drawn in to kill infected cells; as well, there are reports of SARS-CoV-1 and SARS-CoV-2 directly infecting immune cells themselves ( Gu et al., 2005 ; Hu et al., 2012 ; Pontelli et al., 2020 ). As our data are from whole blood RNA, we cannot conclude precisely which of these mechanisms are responsible for the shifts in these genes' expression; however, prior reports suggest that both genes may be involved in viral replication and immune evasion.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it remains to be determined whether PSGL-1 is expressed in SARS coronavirus target cells in the lungs, and, if so, whether its expression can impair viral infection. Interestingly, recent studies suggested that SARS-CoV-2 may also enter and infect human T cells, monocytes, and macrophages, which express high levels of PSGL-1 [ 18 , 19 ]. Infection of T cells by SARS-CoVs could also potentially occur in the scenario of PSGL-1-mediated binding of T cells to inflamed human airway endothelium [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the virus has complex interaction with the innate and adaptive immunity and can directly infect the immune cells. Viral particles and SARS-CoV-2 RNA were found in monocytes, CD4 + T cells, CD8 + T-cells, and B-cells 31,32,33 .…”
Section: Discussionmentioning
confidence: 97%